Văn học Việt Nam thế kỷ XX - Trịnh, Bá Đỉnh (Văn học, 2007)
Giới thiệu tác phẩm của các tác giả: Phạm Quỳnh, Nguyễn Đôn Phục, Nguyễn Trọng Thuật, Nguyễn Văn Vĩnh, Chương Dân, Đàm Xuyên, Nguyễn Mạnh Bổng...